Drug utilization pattern of antimicrobials in OPD of ENT in teaching hospital - K., Ravi Shankar; K., Krishnakanth; Alla, Jagadeesh (International Journal of Basic & Clinical Pharmacology, 2019)
Background: A drug utilization study may be helpful to identify the problems, suggest the remedial measures and promote rational use. Antimicrobials are commonly used to treat infections caused by bacteria, viruses, protozoa and fungi, evidently require huge prescriptions in India. Methods: A prospective, observational study was carried out for a period of four months from February to May 2019 in the Department of ENT (OPD) at NRI Medical College and General Hospital. Prescriptions were collected randomly from around 300 patients attending the ENT outpatient department after obtaining informed consent. The data were collected in the predesigned proforma for analysis. Results: 300 ENT patients were selected for the study, 62% were male and 38% were female. Out of 300 patients 190 ear disorders, 50 nasal, and 60 throat infections. Antimicrobial therapy were most commonly instituted in ear diseases (67.66%), nose (16.95%) and throat (15.37%) respectively. The most commonly used agents were amoxicillin with clavulanic acid- n=295, cefixime- n=1260, gentamicin- n=200, ciprofloxacin- n=157, azithromycin- n=199, nitroimidazoles (metronidazole- n=111). Conclusions: Cefixime and amoxicillin+clavulanic acid combination was the most commonly prescribed antibiotic in our study. Interventions to rectify the use of brand names are necessary to promote rational drug use. An antibiotic policy has to be developed for the doctors in treating infections so that rationality in using the antibiotics will be developed and the occurrence of antibiotic resistance can be reduced.